Use of 3D-Printed Patient-Specific Guide for Latarjet Procedure in Patients With Anterior Shoulder Instability: Technical Note - Vitor La Banca, M.D.; Luiz Giglio, M.D.; Ana Victória Palagi Viganó, M.D.; Luiz Fernando Michaelis, M.D.; João Artur Bonadiman, M.D.; Guilherme Henrique Vieira Lima, M.D.; Roberto Yukio Ikemoto, M.D., Ph.D. (Arthroscopy Techniques, 2023)
Anterior shoulder instability can lead to anterior glenoid bone loss associated with humeral posterior deformity (bipolar bone loss). Latarjet procedure is a commonly used surgical option in such cases. However, the procedure is associated with complications in up 15% of the cases often associated with inadequate positioning of coracoid bone graft and screws. Considering that acknowledgment of patient anatomy and use of surgical planning intraoperatively can reduce such complications, we describe the use of 3D printing tools to obtain a 3D Patient-Specific Surgical Guide to aid in the Latarjet procedure. Such tools present advantages and limitations compared to other tools available, which are also discussed in this article.